Implementation of Character Education from the Perspective of Elementary School Student Characteristics in the Digital Era at SDN Kampungsawah 1 Karawang Student of Master of Administrative Science Study Program - Indra Septia Permana; Veithzal Rivai Zainal; Azis Hakim (Dinasti International Journal of Education Management and Social Science, 2025)
Character education is crucial and a shared focus, particularly in the field of education. Character education must be prepared and implemented from an early age and can be implemented in elementary school. Character education for elementary school students is an effort to prepare a generation with character that can bring about positive change for the Indonesian nation and state. The era of Society 5.0 presents both opportunities for development and challenges that are increasingly challenging compared to previous eras. Therefore, character education must be thoroughly implemented so that students develop character aligned with Islamic teachings and are able to face more complex challenges. This research was conducted using a qualitative library research approach. The data presented in the discussion were obtained through a literature review referring to various scientific sources, such as books, scientific articles, and studies related to the topic. The results are presented directly and objectively through descriptive narrative. Character education at the elementary school level is implemented by instilling religious values ​​in students, promoting a culture of reading and literacy, and conducting extracurricular activities tailored to each student's interests and talents. Character education implementation for elementary school students must be ongoing and supported by teachers so that students become accustomed to the patterns established at school.